Probe: Chinua Achebe’s Things Fall Apart (1958) and No Longer at Ease (1960), and Walter J. Ong’s Thought - Farrell, Thomas J. (New Explorations)

(untitled) (New Explorations Association, 2024)
In a contrapuntal organizational pattern, I discuss Chinua Achebe’s novels Things Fall Apart (1958) and No Longer at Ease (1960), on the one hand, and, on the other, the mature work of the American Jesuit Renaissance specialist and cultural historian and pioneering media ecology theorist Walter J. Ong (1912-2003; Ph.D. in English, Harvard University, 1955) of Saint Louis University. I style this short essay as a “Probe” because it is fundamentally exploratory in nature.